Women’s Learning Trajectories and Their Contribution to Family Stability - Siti Nurhasanah; Hengzhi Hu; Harwati Hashim (Women, Education, and Social Welfare, 2026)
Family stability is increasingly understood as a dynamic outcome shaped by cumulative life experiences rather than static structural conditions. This study examines the contribution of women’s learning trajectories to family stability, conceptualizing learning as a continuous and adaptive process unfolding across the life course. Using a quantitative explanatory design, survey data were collected from 312 adult women actively involved in family functioning. Women’s learning trajectories and family stability were measured as composite variables, and data were analyzed using linear regression and one-way analysis of variance. The results indicate that women’s learning trajectories significantly predict family stability (β = 0.61, p < 0.001), explaining 37% of the variance in the outcome. ANOVA results further reveal significant differences in family stability across low, moderate, and high learning trajectory groups, with the highest stability observed among women with sustained learning engagement over time. These findings provide empirical support for life-course perspectives on learning, demonstrating that cumulative learning experiences among women play a central role in sustaining family stability. The study contributes to research on gender, education, and family by offering a trajectory-oriented quantitative approach with implications for lifelong learning and family-centered policy interventions.